Strategi Komunikasi Perangkat Desa Untuk Meningkatkan Partisipasi Masyarakat Dalam Pembangunan Desa Sesuai Prespektif Al-Qur’an - Ali Akbar Siregar; Irma Yusriani Simamora (Cendekia, 2024)
This research aims to find out the Village Apparatus's communication strategy to increase community participation in the development of Batugana Village, Padang Bolak Julu District, North Padang Lawas Regency. The research method used is qualitative with a descriptive qualitative approach. This research was conducted in Batugana village, Padang Bolak Julu District, North Padang Lawas Regency. The data collection techniques used in this research were primary and secondary data. This research uses theory. The theory used is campaign communication theory. In campaign communication theory, communication activities are carried out to impact a relatively large number of audiences, over a certain period, and through a series of organized communication activities. And the results of this research are the strategies used by village officials to increase community participation, namely by using a participatory approach and a holistic approach. This development planning approach is suitable for building irrigation canals that will irrigate community rice fields. The steps used in the communication strategy include getting to know the community closely, compiling material or discussion topics, and developing methods and objectives that village officials want to carry out in carrying out the communication strategy.